The Important of Planning and Step for Prospective Leadership Proper Planning - Gilang Permata Sukarda; Hadi Supratikta (Journal of Investment Development, Economics and Accounting, 2024)
This paper seeks to to analyze how important planning is for prospective leaders in an organization and to analyze the appropriate planning steps for prospective organizations.The method used is research on succession planning in companies which is qualitative research.It was found that . the speaker planned several stages of the company's sustainable development based on the theory of Susanto et al (2019).Strength and discipline are the main things that a prospective successor must have. In the company, men and women are equal, and candidates for professional succession are not the main choice in this company